Respect for experts or respect for unanimity? The liberal paradox in probabilistic opinion pooling - Frederik Herzberg (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
Amartya Sen (1970) has shown that three natural desiderata for social choice rules are inconsistent: universal domain, respect for unanimity, and respect for some minimal rights - which can be interpreted as either expert rights or liberal rights. Dietrich and List (2008) have generalised this result to the setting of binary judgement aggregation. This paper proves that the liberal paradox holds even in the framework of probabilistic opinion pooling and discusses options to circumvent this impossibility result: restricting the aggregator domain to profiles with no potential for conflicting rights, or considering agendas whose issues are not all mutually interdependent.
Keywords: D71; D82; C11; 330; probabilistic opinion pooling; Sen's liberal paradox; expert rights; liberal rights; unanimity; general aggregation theory